Cardiovascular Health in American Indians and Alaska Natives: A Scientific Statement From the American Heart Association. Issue 25 (23rd June 2020) - Breathett, Khadijah; Sims, Mario; Gross, Marie; Jackson, Elizabeth A.; Jones, Emily J.; Navas-Acien, Ana; Taylor, Herman; Thomas, Kevin L.; Howard, Barbara V.
Abstract : Background: Cardiovascular disease (CVD) is the leading cause of death among American Indians and Alaska Natives. Over the past 50 years, the prevalence of CVD has been rising among American Indians and Alaska Natives. The objective of this statement is to summarize population-level risk factors and management techniques tailored for the American Indian and Alaska Native populations. Methods: PubMed/MEDLINE, the Centers for Disease Control and Prevention, and the annual Heart Disease and Stroke Statistics report from the American Heart Association were used to identify risk factors and interventions specific to American Indians and Alaska Natives. Results: Diabetes mellitus is a major contributor to disproportionately higher rates of coronary heart disease among American Indians and Alaska Natives compared with other racial and ethnic groups. Additional risk factors for CVD include low-density lipoprotein cholesterol levels, hypertension, renal disease, age, and sex. Smoking and exposure to toxic metals are risk factors for some subpopulations. A quarter of American Indians live below the federal poverty line, and thus, low socioeconomic status is an important social determinant of cardiovascular health. Community-based interventions have reduced CVD risk in American Indians and Alaska Natives. Underreporting of American Indian and Alaska Native race could underestimate the extent of CVD in this population. Conclusions: Prevention and treatment of CVD in American Indians and Alaska Natives should focus on control of risk factors and community-based interventions that address social determinants of health, particularly among individuals with diabetes mellitus. Accurate reporting of race/ethnicity is encouraged to address race-specific risk factors.